Estudo in silico e in vitro do efeito antitumoral da 1,4- naftoquinona (cnn1) em modelos experimentais de leucemia mieloide crônica resistentes à quimioterapia - Portilho, Adrhyann Jullyanne de Sousa (2022)
Chronic Myeloid Leukemia (CML) is myeloproliferative disease in which clonal expansion of hematopoietic stem cells (CTHs). It is characterized by the formation of the Philadelphia chromosome (Ph+), responsible for caused CML. Currently, chemotherapy resistance has been one the biggest obstacles in the treatment of patients with CML, around 30% - 40% of patients develop resistance or intolerance to tyrosine kinase inhibitors (TKIs) during treatment. Therefore, still is need developmente and search of new drugs with greater effective potency and low toxic effects. In this scenario, naphthoquinones are target of several studies due to their pharmacological activities, demonstrating excellent antitumor activity in different type of cancer. Therefore, the present study aimed to investigate, through in silico and in vitro techniques, the antitumor effect of 1,4-naphthoquinone (CNN1) in chemotherapyresistant Chronic Myeloid Leukemia. Initially, the cytotoxic effect of CNN1 was evaluated against a panel of different tumor cell lines, imatinib mesylate, and the active metabolites of irinotecan (SN-38) were used as positive controls. Next, CNN1 pharmacokinetic and pharmacodynamic analyzes were performed using in silico approaches, as well as molecular docking analysis. Afterward, the mechanism of cell death caused by CNN1 was investigated through the analysis of morphological changes, DNA fragmentation, cell cycle, membrane integrity, mitochondrial membrane potential, and cell death test by marking with annexinAlexa Fluor® 488/iodide of propidium (Annexin/IP) by flow cytometry, in addition, the genotoxic effect of CNN1 was evaluated. The RT-qPCR method was used to evaluate of gene expression of the TOP1, ABCB1, BRC-ABL1 and H2AFX genes. The results of this study, demonstrated excellent antitumor activity of CNN1 in chemosensitive leukemia strains K-562 (IC50 = 1.12 µM) and chemoresistant FEPS (IC50 = 0.60 µM) and lower activity in the nonneoplastic cell line MRC-5 (IC50 = 15.45 µM). In silico studies, the CNN1 molecule showed good ADME/T properties, indicating good oral bioavailability and the pharmacodynamic results showed that CNN1 has a pharmacological target to Topoisomerase I, then molecular docking analysis revealed that CNN1 has a binding affinity of -11.94 kcal/mol with Topoisomerase I and was also able to reduce the level of TOP1 gene expression (p<0.01). As for the investigation of cell death, CNN1 induced morphological changes, membrane rupture (p<0.001) and mitochondrial depolarization (p<0.001) in the K-562 and FEPS strains. Sequentially, CNN1 caused DNA fragmentation (p<0.001), accumulation of cells in the G2/M phase (p<0.001) and induced genotoxic damage (p<0.001) similar to SN-38, however, CNN1 was less toxic to cells in peripheral blood mononuclear cells and MRC-5. Further results showed an increase in the population of apoptotic cells (p<0.001), confirmed by annexin/IP labeling. Furthermore, treatment with CNN1 induced an increase in H2AFX gene expression (p<0.001) in both strains. Therefore, our results demonstrate that CNN1 has a promising anticancer activity for the treatment of ITQ-refractory and/or intolerant patients with CML, and may also be an alternative treatment for patients who develop adverse effects caused by irinotecan